Backyard Poultry Farming changing the face of rural and tribal livelihoods - Rajkumar, U; Rama Rao, S V; Sharma, R P (Indian Farming, 2015)
Vanaraja and Gramapriya birds are performing well in different climatic conditions across the country. The rural and tribal people are earning a subsidiary income to the family. These chicken varieties are playing a vital role in the livelihoods of the rural and tribal people of India. Based on the quantity of natural food base available, body weight and health of the bird for input and on the basis of productivity and body weight of bird for output, an economic analysis was carried out for 12 and 15 weeks for male birds of Vanaraja and Gramapriya, respectively. The layers are kept for complete laying cycle of 72 weeks. The farmer can earn a net profit of Rs. 32-44/ bird on males and 200-250/bird on female birds in Vanraja and a Rs. 11 and up to 380 per bird in Gramapriya, respectively.